Assesment impacted canines of two-dimensional and three-dimensional radiographic techniques: Penilaian impaksi gigi kaninus dari teknik radiografi dua dimensi dan tiga dimensi - Marini Arisandy; Yunus, Barunawaty (Makassar Dental Journal, 2024)
Canine tooth impaction plays an important role in smile aesthetics and functional occlusion, and can cause dental and skeletal malocclusion. Treatment planning for canine tooth impaction cases is complex and is influenced by various factors, including the inclination, angle, position, depth of impaction, as well as the surrounding bone density. For a more precise evaluation, imaging is the recommended tool, which includes 2D radiographs, as well as 3D imaging using. This literature review presents current information on the assessment of canine tooth impaction by considering appropriate diagnostic imaging options to support more adequate treatment planning with consideration of radiation dose. It is concluded that although conventional radiographic modalities are able to provide accurate diagnosis regarding the morphology of the apex, apex location, and inclination of canine tooth impaction, cone beam computed tomography (CBCT) offers a higher degree of accuracy in determining other parameters associated with canine tooth impaction. Therefore, the use of CBCT may be the preferred option for a more comprehensive and accurate evaluation of canine tooth impaction cases.